HIF-1α Overexpression Induces Angiogenesis in Mesenchymal Stem Cells - Razban, Vahid (Mary Ann Liebert, Inc., 2012)
Stem cell therapy continues to be an innovative and promising strategy for heart failure. Stem cell injection alone, however, is hampered by poor cell survival and differentiation. This study was aimed to explore the possibility of improving stem cell therapy through genetic modification of stem cells, in order for them to promote angiogenesis in an auto- and paracrine manner under hypoxic conditions. Hypoxia inducible factor-1α was overexpressed in bone marrow-derived mesenchymal stem cells (MSCs) by stable transduction using a lentiviral vector. Under hypoxic and normoxic conditions, the vascular endothelial growth factor (VEGF) concentration in the cells' supernatant was measured by an enzyme-linked immunosorbent assay. Migration was assayed by wound healing and c-Met expression by flow cytometry. Tube formation was evaluated on a Matrigel basement membrane. The concentration of VEGF was significantly increased in the supernatant of HIF-1α–overexpressing MSCs; this medium was significantly more effective in inducing endothelial cell migration compared to untransduced MSCs. Transduced cells showed increased levels of c-Met expression and were more efficient at tube formation. However, no indication of differentiation toward an endothelial phenotype was observed. This study indicated that genetic modification of MSCs by HIF-1α overexpression has the potential to improve components of the angiogenesis process under a hypoxic condition by paracrine and autocrine mechanisms.